Assessment of the body response to specific fatigue exercise protocol SAFT90 in U16 soccer players - Sládecková, B.; Botek, M.; Krejci, J.; Lehnert, M. (Acta Gymnica, 2019)
Background: SAFT90 is a specific multidirectional fatigue protocol that imitates the internal and external load of soccer match-play.